Prevalence of depression, anxiety, and insomnia among healthcare workers during the COVID-19 pandemic: A systematic review and meta-analysis - Pappa, Sofia; Ntella, Vasiliki; Giannakas, Timoleon; Giannakoulis, Vassilis G.; Papoutsi, Eleni; Katsaounou, Paraskevi (Brain, behavior, and immunity, 2020)
•At least one in five healthcare professionals report symptoms of depression and anxiety.•Almost four in ten healthcare workers experience sleeping difficulties and/or insomnia.•Rates of anxiety and depression were higher for female healthcare workers and nursing staff.•Milder mood symptoms are common and screening should aim to identify mild and sub-threshold syndromes. COVID-19 pandemic has the potential to significantly affect the mental health of healthcare workers (HCWs), who stand in the frontline of this crisis. It is, therefore, an immediate priority to monitor rates of mood, sleep and other mental health issues in order to understand mediating factors and inform tailored interventions. The aim of this review is to synthesize and analyze existing evidence on the prevalence of depression, anxiety and insomnia among HCWs during the Covid-19 outbreak. A systematic search of literature databases was conducted up to April 17th, 2020. Two reviewers independently assessed full-text articles according to predefined criteria. Risk of bias for each individual study was assessed and data pooled using random-effects meta-analyses to estimate the prevalence of specific mental health problems. The review protocol is registered in PROSPERO and is available online. Thirteen studies were included in the analysis with a combined total of 33,062 participants. Anxiety was assessed in 12 studies, with a pooled prevalence of 23·2% and depression in 10 studies, with a prevalence rate of 22·8%. A subgroup analysis revealed gender and occupational differences with female HCPs and nurses exhibiting higher rates of affective symptoms compared to male and medical staff respectively. Finally, insomnia prevalence was estimated at 38·9% across 5 studies. Early evidence suggests that a considerable proportion of HCWs experience mood and sleep disturbances during this outbreak, stressing the need to establish ways to mitigate mental health risks and adjust interventions under pandemic conditions.